Unravelling the fetal origins hypothesis: is there really an inverse association between birthweight and subsequent blood pressure? - Huxley, R; Neil, A; Collins, R (2002)
BACKGROUND: The association between birthweight and subsequent blood pressure levels has been considered to provide some of the strongest, and most consistent, support for the "fetal origins" hypothesis of adult disease. It had been estimated that a 1 kg higher birthweight is typically associated with a 2-4 mm Hg lower systolic blood pressure. METHODS: 55 studies that had reported regression coefficients of systolic blood pressure on birthweight (with 48 further studies that reported only the direction of this association), and seven such studies within twin pairs, were identified. Each study was weighted according to the inverse of the variance of the regression coefficient (ie, "statistical size"), and combined using a "fixed effects" approach. FINDINGS: Among the 55 studies that reported regression coefficients, there was a clear trend (p<0.0001) towards weaker associations in the larger studies: -1.9 mm Hg/kg in those with less than about 1000 participants; -1.5 mm Hg/kg with about 1000-3000 participants; and -0.6 mm Hg/kg with more than 3000 participants. By contrast with the inverse associations reported in 52 of these 55 studies, only 25 of the 48 studies that did not report regression coefficients found an inverse association (p<0.0001 for heterogeneity). Almost all of these regression coefficients had been adjusted for current weight (whereas few were adjusted for potential confounding factors), and removal of this adjustment in the larger studies reduced the estimated association to -0.4 mm Hg/kg. For studies within monozygotic twin pairs, the combined estimate was -0.6 mm Hg/kg with adjustment for current weight, and was also reduced without this adjustment. INTERPRETATION: Claims of a strong inverse association between birthweight and subsequent blood pressure may chiefly reflect the impact of random error, selective emphasis of particular results, and inappropriate adjustment for current weight and for confounding factors. These findings suggest that birthweight is of little relevance to blood pressure levels in later life.